Acute cognitive postconcussive symptoms follow longer recovery trajectories than somatic postconcussive symptoms in young children. (23rd February 2020) - Teh, Zoe; Takagi, Michael; Hearps, Stephen. J. C.; Babl, Franz E.; Anderson, Nicholas; Clarke, Cathriona; Davis, Gavin A.; Dunne, Kevin; Rausa, Vanessa C.; Anderson, Vicki
ABSTRACT: Objective : To investigate somatic and cognitive postconcussive symptoms (PCS) using the symptom evaluation subtest (cSCAT3-SE) of the Child Sports Concussion Assessment Tool 3 (Child SCAT) in tracking PCS up to 2 weeks postinjury. Methods : A total of 96 participants aged 5 to 12 years ( Mage = 9.55, SD = 2.20) completed three assessment time points: 48 h postinjury (T0), 2 to 4 days postinjury (T1), and 2 weeks postinjury (T2). The Wilcoxon signed-rank test was used to analyze differences between cognitive and somatic symptoms over time, while the Friedman test was used to analyze differences within symptom type over time. Results : Cognitive PCS were found to be significantly higher than somatic PCS at all assessment time points and were also found to significantly decline from 4 days onwards postinjury; in contrast, somatic PCS significantly declined as early as 48 hpostinjury. Discussion : Differences between cognitive and somatic PCS emerge as early as a few days postinjury, with cognitive PCS being more persistent than somatic PCS across 2 weeks. Research in symptom-specific interventions may be of benefit in helping young children manage severe PCS as early as 2 weeks postinjury.